Un modelo para la gestión de la información y la tecnología en la Universidad Nacional - Arthur Giesberts; Carlos Francisco Carranza; Ronald Miranda-Chavarría (Universidad Nacional, Costa Rica, 2004)
In public universities, information, technology and communications (ITC) management, is not to be considered an issue concerning experts only; it needs to be under the direction of academic authorities and must conform with the management model of the institution, particularly with its degree of decentralization and the rendering of accounts. The model must develop strategic skills in information and technology matters for academic and management processes, and for support services. The ITC management process includes planning and organization; the acquisition and implementation of technological and information systems; the delivery and support of related services and, finally, a monitoring stage. We propose here a decentralized organization model that would include an entity for advisory assistance to the Rectorship, and which would be in charge of the strategic information and of guiding the information and technology management model. The vicerectorships will define the nature of the information required to feed academic and management processes, and support systems, while an operational entity manages internal networks, data and the functioning and safety of information systems. The model presented here is a proposal to be used at Universidad Nacional as part of an improvement process in generation systems, data processing and the use of these data in academic activities and university management.